2010
DOI: 10.3109/13561820.2010.505350
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of power: implications for interprofessional education

Abstract: Interprofessional education (IPE) is considered a key mechanism in enhancing communication and practice among health care providers, optimizing participation in clinical decision making and improving the delivery of care. An important, though under-explored, factor connected to this form of education is the unequal power relations that exist between the health and the social care professions. Drawing on data from the evaluation of a large multi-site IPE initiative, we use Witz's model of professional closure (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
166
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 282 publications
(185 citation statements)
references
References 14 publications
6
166
0
6
Order By: Relevance
“…Physicians who were found to have negative attitudes to IPW were also found to have a greater perception of their role as main decision makers in the healthcare team (Abramson & Mizrahi, 2003;Reid et al, 2006;Rice et al, 2010;Russell, Nyhof-Young, Abosh, & Robinson, 2006). The implications of perceptions of power on attitudes to IPE was discussed by Baker et al, (2011). The results of their study suggested that this perception may have negatively impacted on attitudes to IPE, as physicians were reported to be less engaged in IPE initiatives within the healthcare setting, in comparison to nurses and AHPs.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…Physicians who were found to have negative attitudes to IPW were also found to have a greater perception of their role as main decision makers in the healthcare team (Abramson & Mizrahi, 2003;Reid et al, 2006;Rice et al, 2010;Russell, Nyhof-Young, Abosh, & Robinson, 2006). The implications of perceptions of power on attitudes to IPE was discussed by Baker et al, (2011). The results of their study suggested that this perception may have negatively impacted on attitudes to IPE, as physicians were reported to be less engaged in IPE initiatives within the healthcare setting, in comparison to nurses and AHPs.…”
Section: Resultsmentioning
confidence: 69%
“…Fourteen of these studies included health and social care staff as research participants (Table 2). Although four studies included attitudes to IPE and IPW, the study by Baker et al, (2011) was the only study to include health and social care staff attitudes to both IPW and IPE for students within the context of the healthcare setting. Despite these limitations, this review was valuable in identifying two main common themes which included the effect of:…”
Section: Resultsmentioning
confidence: 99%
“…Lack of communication and awareness of interprofessional roles has been shown to reinforce power differentials within the interprofessional team, leading to a lack of participation in interprofessional education and decreased interprofessional collaboration (Baker, Egan-Lee, Martimianakis, & Reeves, 2011). Lack of role awareness, poor communication, and insufficient collaboration have been associated with a decreased acceptance of pharmacy roles within primary health care teams in the United States and Canada (Patterson et al, 2015;Schindel et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Para Milburn & Colyer (2008), a educação interprofissional envolve diferentes grupos profissionais na aprendizagem interativa para o desenvolvimento de habilidades como comunicação, negociação, resolução de problemas, trabalho em equipe e gestão de conflitos, enquanto que na aprendizagem compartilhada participantes são atraídos, a partir de dois ou mais grupos profissionais, na qual o ensino e aprendizagem se centra no conteúdo comum do currículo e não necessariamente no desenvolvimento de habilidades de interação. Diferentes autores têm destacado uma série de barreiras significativas à educação interprofissional que vão desde as estruturais, causadas e mantidas dentro ou entre sistemas de saúde e de educação, até aquelas que são construídas dentro das culturas profissionais ou relacionadas às diferenças de atitudes frente às práticas colaborativas (BAKER et al, 2011;FEWSTER-THUENTE, 2011;GILBERT, 2005;HALL, 2005;BURING et al, 2009). Tais dificuldades existem ocorrem, mesmo nas experiências em que se fez opção por desenhos mais interprofissionais, como é o caso da FCE/UnB que busca, sistematicamente, investir na formação do seu quadro de professores e criar oportunidades para discussão das práticas docentes e sua aproximação com as orientações metodológicas e as bases conceituais que fundamentaram os projetos pedagógicos dos cursos.…”
Section: Formação Docente Na áRea Da Saúde E a Educação Interprofissiunclassified